Trabectedin: Supportive care strategies and safety profile. Issue 3 (June 2015) - Jordan, Karin; Jahn, Franziska; Jordan, Berit; Kegel, Thomas; Müller-Tidow, Carsten; Rüssel, Jörn
Highlights: Trabectedin is approved for soft tissue sarcoma and ovarian cancer. The most commonly observed toxicities include neutropenia and elevation of liver tansaminases. The appropriate use of supportive care strategies can reduce the side effects. The hepatic metabolism must be kept in mind (CYP3A4). Abstract: Trabectedin is an approved antineoplastic agent for the treatment of adult patients with advanced soft tissue sarcomas or in combination with pegylated liposomal doxorubicin (PLD) in patients with relapsed platinum sensitive ovarian cancer. The mechanism of action is still not fully understood but many typical side effects seen with other chemotherapy drugs are less common, mild or unreported. Although this apparent favorable safety profile suggests a well-tolerated and manageable therapeutic option in the palliative care setting, trabectedin does have specific adverse side effects which can be hazardous for individual patients. The most commonly observed toxicities with trabectedin include neutropenia, nausea, vomiting, and increases in liver transaminases, anemia, fatigue, thrombocytopenia, anorexia and diarrhea. However, for most patients the appropriate use of supportive care strategies can reduce or overcome these side effects. We present a concise review of the safety data of trabectedin with the corresponding overview of the supportive care strategies.